2006
DOI: 10.1016/s1470-2045(06)70803-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease after nephrectomy in patients with renal cortical tumours: a retrospective cohort study

Abstract: SummaryBackground-Chronic kidney disease is a graded and independent risk factor for substantial comorbidity and death. We aimed to examine new onset of chronic kidney disease in patients with small, renal cortical tumours undergoing radical or partial nephrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
903
1
45

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,474 publications
(976 citation statements)
references
References 43 publications
27
903
1
45
Order By: Relevance
“…Nevertheless, whether or not to excise a rim of healthy parenchyma, theoretically necessary to avoid the risk of a positive SM and local recurrence, is a matter of great controversy, and recent reports concluded that the width of the resection margins does not correlate with disease progression and that if the tumor is completely excised, the margin size is irrelevant, thus providing an intriguing insight into the possibility of bluntly excising the tumor, such as a TE [13,14]. Moreover, from a functional point of view, a narrower excision margin in RCC tumors would lead to additional parenchymal tissue preservation, and a recent report by Huang et al showed that the new onset of GFR of <60 ml/min and of <45 ml/min per 1.73 m 2 in patients with small RCC tumors can occur also after standard partial nephrectomy in 20% and 5% of cases at 3-yr follow-up, respectively [27].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, whether or not to excise a rim of healthy parenchyma, theoretically necessary to avoid the risk of a positive SM and local recurrence, is a matter of great controversy, and recent reports concluded that the width of the resection margins does not correlate with disease progression and that if the tumor is completely excised, the margin size is irrelevant, thus providing an intriguing insight into the possibility of bluntly excising the tumor, such as a TE [13,14]. Moreover, from a functional point of view, a narrower excision margin in RCC tumors would lead to additional parenchymal tissue preservation, and a recent report by Huang et al showed that the new onset of GFR of <60 ml/min and of <45 ml/min per 1.73 m 2 in patients with small RCC tumors can occur also after standard partial nephrectomy in 20% and 5% of cases at 3-yr follow-up, respectively [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the importance of nephron-sparing surgery focuses not only on avoiding chronic renal insufficiency, but also to decrease the incidence of cardiovascular events and death. 8,9,10 Therefore, in patients with a renal mass ≤ 4cm (cT1a), partial nephrectomy is the new gold standard. It has even been suggested that tumors <7cm (cT1b) should be managed with parital nephrectomy when surgically feasible.…”
Section: Review Of Management Options For the Ct1 Renal Massmentioning
confidence: 99%
“…And third, it has also been found that a RN puts patients at an increased risk for chronic kidney disease [35]. Huang and colleagues did a retrospective cohort study of 662 patients undergoing elective partial or radical nephrectomy for a solitary, renal cortical tumor less than 4 cm [36]. Upon further examination, they noted that 171 (26%) of these patients had pre-existing chronic kidney disease prior to surgery [36].…”
Section: Kidney Cancermentioning
confidence: 99%
“…Huang and colleagues did a retrospective cohort study of 662 patients undergoing elective partial or radical nephrectomy for a solitary, renal cortical tumor less than 4 cm [36]. Upon further examination, they noted that 171 (26%) of these patients had pre-existing chronic kidney disease prior to surgery [36]. By following these 171 patients for 3 years, Huang et al discovered that patients who underwent a RN had a 65% chance of developing chronic kidney disease as opposed to a 20% chance with a PN [36].…”
Section: Kidney Cancermentioning
confidence: 99%
See 1 more Smart Citation